Method for modifying polymer recovered material
By adding a radical initiator and a bisunsaturated hydrocarbon compound to the polyolefin composition recovered after consumption and performing extrusion treatment, the problem of modified polyolefin recovery in the prior art is solved, and the processability and mechanical properties of the material are improved.
Patent Information
- Application Number
- CN202380040281.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-16
- Filing Date
- 2023-05-15
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art is difficult to effectively modify post-consumer recycling polyolefins, especially when treating mixtures of different plastics and contaminants, and it is difficult to provide recycled plastic materials with wide application properties.
Modify the polyolefin composition by providing a method including adding a radical initiator and a bisunsaturated hydrocarbon compound to the post-consumed polyolefin composition and extruding within a specific temperature range, reducing its melt flow rate, increasing the weight average molecular weight and molecular weight distribution, and enhancing its mechanical properties.
The processability and reusability of the modified polyolefin composition are achieved, the melt flow rate is reduced, and the mechanical properties such as rigidity and toughness are improved, which are suitable for the manufacturing of various products.
Smart Images

Figure CN119836446A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for modifying a polyolefin composition based on post-consumer recycled polypropylene. The present invention also relates to a modified polyolefin composition obtained by the method, and the use of the modified polyolefin composition in the manufacture of articles, and the corresponding articles. Background Art
[0002] The challenge of dealing with accumulated plastic waste and the corresponding environmental issues have received widespread attention from the public and professionals. Therefore, the recycling of plastic materials has become an important topic, which can transform plastic waste into a resource for new plastic products. Therefore, it is possible to combine environmental and economic aspects when recycling and reusing plastic materials.
[0003] Although the recycling of plastic materials has begun since the mid-90s through the implementation of collection systems that allow a more targeted collection of plastic materials and their separation from other household waste materials, the reuse of plastic materials originating from plastic waste is still limited. So-called post-consumer recycled (PCR) plastic materials usually contain a mixture of different plastics and several contaminant materials. These mixtures usually require a pretreatment step for mechanical recycling (i.e. material sorting and cleaning) before further preparation methods. Moreover, many of the methods used to date are generally limited to the use of relatively homogeneous plastic materials with a low content of contaminants. In addition, they usually do not provide recycled plastic materials with the properties necessary for a wide range of applications.
[0004] Many methods for modifying post-consumer recycled plastic materials are described in the art. For example, European patent application EP3757152A1 discloses a method for providing a controlled rheology modified mixed-plastic-polyethylene blend having a melt flow rate of 0.1 to 0.45 g / 10 min (ISO 1133, 2.16 kg load, 190° C.) from a waste stream, wherein the mixed-plastic-polyethylene reactant blend is melt blended with a peroxide.
[0005] However, there is a general need for further modification methods of waste plastic materials, particularly post-consumer recycled plastic materials.
[0006] Polyolefins are the main plastic material in post-consumer recycling. Therefore, there is a strong need to provide methods for modifying polyolefins from post-consumer recycled plastic materials. These methods should have high tolerance to the ratio of propylene polymer to ethylene polymer and also should have high tolerance to the presence of non-polyolefin plastic materials and other contaminants present in post-consumer recycled plastic materials.
[0007] For the reuse of recycled polyolefins, several properties are very important. These properties are particularly related to the rheological and mechanical properties of the polyolefins, which make them processable and suitable for the preparation of new articles. Therefore, there is a particular need for polyolefin modification methods that produce polyolefins with these properties. Summary of the invention
[0008] The object of the present invention is to provide a method for solving the above problems and to provide corresponding modified polyolefins.
[0009] Therefore, the present invention provides a method for modifying a post-consumer recycled polyolefin composition comprising the steps of:
[0010] (A) providing a post-consumer recycled polyolefin composition having an initial melt flow rate MFR measured according to ISO 1133 at 2.16 kg load, 230° C. in the range of 1.0 to 100 g / 10 min 2 (1), and based on the total weight of the post-consumer recycled polyolefin composition, as determined by FTIR spectroscopy, comprising
[0011] (a) at least 50 wt.% of one or more propylene (co)polymer components, and
[0012] (b) up to 50 wt. % of one or more ethylene (co)polymer components;
[0013] (B) adding 0.10 to 1.50 wt % of a free radical initiator, based on the total weight of the post-consumer recycled polyolefin composition, to the post-consumer recycled polyolefin composition and optionally mixing the components to form a mixture (1);
[0014] (C) adding 0.05 wt% to 0.50 wt% of a di-unsaturated hydrocarbon compound having the general formula (1), based on the total weight of the post-consumer recycled polyolefin composition,
[0015] (1)CH 2 =CH-(R)-CH=CH 2 ,
[0016] wherein R may be present or absent, and if present, R is an aliphatic or aromatic hydrocarbon group containing 1 to 6 carbon atoms,
[0017] and mixing the components to form a mixture (2); and
[0018] (D) extruding the mixture (2) at a temperature in the range of 180°C to 300°C to obtain a final melt flow rate MFR measured according to ISO 1133 at 230°C under a load of 2.16 kg 2 (2) modified polyolefin composition;
[0019] Where MFR 2 (2):MFR 2 The ratio of (1) is less than 1.00.
[0020] The present invention also provides a modified polyolefin composition obtained by the method, use of the modified polyolefin composition in manufacturing products, and corresponding products. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Shown are the molecular weight distribution (MWD, expressed as dW / dlog(M)) of inventive example IE7 and two comparative examples CE4 and CE5, as well as the radius of gyration (expressed as logRg) predicted for inventive example IE7 for a fully linear polymer. DETAILED DESCRIPTION
[0022] The present invention provides a method for modifying a post-consumer recycled polyolefin composition. The method uses a post-consumer recycled (PCR) polyolefin composition and introduces long chain branching into the polyolefin. The modified polyolefin composition is characterized by improved properties in terms of processability and reuse of the polyolefin composition. The method reduces the melt flow rate of the polyolefin composition, increases its weight average molecular weight (Mw) and widens the molecular weight distribution (MWD), increasing the polydispersity Mw / Mn. This makes the handling of the composition easier in the production of new products and improves the mechanical properties of the product, such as rigidity and toughness.
[0023] Post-consumer recycled (PCR) polyolefin compositions
[0024] In step (A) of the process of the present invention, a post-consumer recycled polyolefin composition is provided.
[0025] According to the present invention, a post-consumer recycled (PCR) polyolefin composition means a composition comprising polyolefins obtained from consumer waste. Thus, the post-consumer recycled polyolefins have completed at least a first use cycle (or life cycle), i.e. have reached their first purpose. Post-consumer recycled polyolefins are different from virgin polyolefins (i.e. newly produced materials, which have not been recycled), virgin polyolefins. Post-consumer recycled polyolefins are also different from industrial waste (i.e. manufacturing waste, which usually does not reach the hands of consumers).
[0026] Virgin and recycled materials can be easily differentiated based on the presence of contaminants such as limonene, fatty acids, paper and / or wood and other contaminants or often based on their ash content. Polyolefins such as polypropylene-polyethylene blends can be further differentiated by the possible presence of non-polyolefin polymers such as polystyrene and / or polyamide.
[0027] The method of the present invention is suitable for use with compositions comprising a wide range of propylene polymer to ethylene polymer ratios. Based on the gross weight of a post-consumer recycled polyolefin composition and measured by Fourier transform infrared (FTIR) spectroscopy, the post-consumer recycled polyolefin composition comprises,
[0028] (a) at least 50 wt.% of one or more propylene (co)polymer components, and
[0029] (b) up to 50 wt. % of one or more ethylene (co)polymer components.
[0030] Preferably, the one or more ethylene (co)polymer components are present in the post-consumer recycled polyolefin composition in an amount of at least 1 wt. % (i.e., 1 to 50 wt. %), based on the total weight of the post-consumer recycled polyolefin composition, as determined by FTIR spectroscopy.
[0031] The post-consumer recycled polyolefin composition preferably comprises a mixture (eg a polymer blend) of one or more propylene (co)polymer components and one or more ethylene (co)polymer components.
[0032] Since it is not possible to determine the propylene (co)polymer and ethylene (co)polymer contents directly, the weight contents are determined from equivalent ratios calibrated with isotactic polypropylene (iPP) homopolymer and high density polyethylene (HDPE).
[0033] In one embodiment, the post-consumer recycled polyolefin composition comprises, as determined by FTIR spectroscopy, based on the total weight of the post-consumer recycled polyolefin composition,
[0034] (a) 50 to 98 wt%, preferably 52 to 96 wt%, more preferably 53 to 95 wt% of one or more propylene (co)polymer components, and
[0035] (b) 2 to 50 wt%, preferably 4 to 48 wt%, more preferably 5 to 47 wt% of one or more ethylene (co)polymer components.
[0036] The (co)polymer component preferably has a high degree of crystallinity as defined below. However, a less crystalline or non-crystalline copolymer component may additionally be present in the post-consumer recycled polyolefin composition.
[0037] Preferably, the post-consumer recycled polyolefin composition comprises a crystalline fraction (CF) measured according to the CRYSTEX QC method of ISO 6427 Annex B, in an amount ranging from 75 to 98 wt.-%, based on the total weight of the post-consumer recycled polyolefin composition. The less crystalline or non-crystalline copolymer component accounts for the majority of the soluble fraction (SF) measured according to the CRYSTEX QC method of ISO 6427 Annex B, in an amount ranging from 2 to 25 wt.-%, based on the total weight of the post-consumer recycled polyolefin composition.
[0038] The post-consumer recycled polyolefin composition may also comprise an ethylene content of the crystalline fraction (C2(CF)), which is determined according to FTIR during CRYSTEX analysis, and the amount of ethylene content is in the range of 3 to 60 wt.-%, preferably 5 to 55 wt.-%, more preferably 6 to 50 wt.-%, based on the total weight of the crystalline fraction of the post-consumer recycled polyolefin composition.
[0039] The post-consumer recycled polyolefin composition may also comprise an ethylene content in the soluble fraction (C2(SF)) determined according to FTIR during CRYSTEX analysis, in an amount ranging from 20 to 50 wt%, preferably from 23 to 47 wt%, more preferably from 25 to 45 wt%, based on the total weight of the soluble fraction of the post-consumer recycled polyolefin composition.
[0040] Propylene (co)polymer component
[0041] According to the present invention, "propylene (co)polymer component" means a propylene homopolymer component and a propylene copolymer component as well as combinations thereof, such as copolymers or blends.
[0042] The expression "propylene homopolymer" means that the 13 C{ 1 The propylene polymer is composed of at least 99.0 wt%, preferably at least 99.5 wt%, and more preferably at least 99.8 wt% of propylene monomer units, based on the total weight of the propylene polymer, as determined by H} nuclear magnetic resonance (NMR) spectroscopy. In one embodiment, only propylene monomer units can be detected in the propylene homopolymer.
[0043] Based on its crystal structure, the propylene homopolymer can exist as isotactic, syndiotactic or atactic propylene homopolymer.
[0044] Preferably, the propylene homopolymer has a high degree of crystallinity. Preferably, the propylene homopolymer is an isotactic propylene homopolymer, i.e. 13 C{ 1A propylene homopolymer having isotacticity at the pentad level, measured by H} NMR spectroscopy and reported as the percentage of isotactic pentad (mmmm) sequences relative to all pentad sequences, of 95 to 98%, preferably 95.5 to 98%, more preferably 96 to 97.5%.
[0045] The expression "propylene copolymer" means a propylene polymer generally comprising propylene monomer units and other comonomer units, preferably ethylene comonomer units and / or one or more α-olefin comonomer units having 4 to 10 carbon atoms, most preferably ethylene comonomer units. 13 C{ 1 The content of propylene monomer units in the propylene copolymer is at least 70% by weight, based on the total weight of the propylene copolymer, as determined by H}-NMR spectroscopy, or by quantitative 13 C{ 1 H}-NMR spectroscopy, based on the total molar content of the propylene copolymer, is at least 70 mol%.
[0046] Preferably, the propylene copolymer is an isotactic propylene copolymer, i.e. 1 The propylene copolymer has isotacticity at the pentad level, measured by H}-NMR spectroscopy and reported as the percentage of isotactic pentad (mmmm) sequences relative to all pentad sequences, of 95 to 98%, preferably 95.5 to 98%, more preferably 96 to 97.5%.
[0047] In one embodiment of the present invention, the at least one propylene (co)polymer component is an isotactic propylene homopolymer. In another embodiment of the present invention, the at least one propylene (co)polymer component is an isotactic propylene copolymer of propylene and a comonomer selected from ethylene and / or one or more α-olefins having 4 to 10 carbon atoms, preferably ethylene, wherein the propylene copolymer is propylene and / or ethylene ... 13 C{ 1 The copolymer preferably contains 0.1 to 27 mol %, more preferably 0.1 to 20 mol % of the comonomer, as determined by H}-NMR spectroscopy.
[0048] Ethylene (co)polymer components
[0049] According to the present invention, the ethylene (co)polymer component refers to an ethylene homopolymer component and an ethylene copolymer component as well as combinations thereof, such as copolymers or blends.
[0050] The expression "ethylene homopolymer" means that the 13 C{ 1The ethylene polymer is composed of at least 99.0 wt %, preferably at least 99.5 wt %, and more preferably at least 99.8 wt % ethylene monomer units, based on the total weight of the ethylene polymer, as determined by H}-NMR spectroscopy. In one embodiment, only ethylene monomer units can be detected in the ethylene homopolymer.
[0051] The expression "ethylene copolymer" means an ethylene polymer generally comprising ethylene monomer units and other comonomer units, preferably one or more α-olefin comonomer units having 3 to 10 carbon atoms. 13 C{ 1 The content of ethylene monomer units in the ethylene copolymer is at least 70% by weight, based on the total weight of the ethylene copolymer, as determined by H}-NMR spectroscopy, or by quantitative 13 C{ 1 H}-NMR spectroscopy, based on the total molar content of the ethylene copolymer, is at least 75 mol %.
[0052] Preferably, the ethylene (co)polymer has a high crystallinity of at least 40%, which is determined by differential scanning calorimetry (DSC) and assuming that the melting enthalpy of a completely crystalline ethylene polymer is 293 J / g.
[0053] In one embodiment of the present invention, the at least one ethylene (co)polymer component is an ethylene homopolymer having a crystallinity of 40% to 90%, the crystallinity being determined by differential scanning calorimetry (DSC) and assuming a melting enthalpy of 293 J / g for a completely crystalline ethylene polymer. In another embodiment of the present invention, the at least one ethylene (co)polymer component is an ethylene copolymer of ethylene and a comonomer selected from one or more α-olefins having 3 to 10 carbon atoms, wherein the crystallinity is determined by quantitative 13 C{ 1 The copolymer preferably contains 0.1 to 20 mol %, more preferably 0.1 to 15 mol % of comonomer, as determined by H}-NMR spectroscopy, and has a crystallinity of 40 to 90 %, which is determined by differential scanning calorimetry (DSC) and assuming a melting enthalpy of 293 J / g for a completely crystalline ethylene polymer.
[0054] Other components
[0055] Furthermore, the post-consumer recycled polyolefin composition preferably comprises one or more of the following, based on the total weight of the post-consumer recycled polyolefin composition:
[0056] (c) 0.1 to 100 ppm, preferably 0.1 to 50 ppm, more preferably 0.1 to 20 ppm, most preferably 0.1 to 5 ppm limonene as determined by solid phase microextraction (HS-SPME-GC-MS);
[0057] (d) 0.1 to 100 ppm, preferably 0.1 to 50 ppm, more preferably 0.1 to 20 ppm, most preferably 0.1 to 5 ppm fatty acids as determined by solid phase microextraction (HS-SPME-GC-MS);
[0058] (e) 0.1 to 10 wt. %, preferably 0.1 to 5 wt. %, more preferably 0.1 to 3 wt. % of non-polyolefin polymers, as determined by FTIR spectroscopy; in particular, 0.1 to 3 wt. % of polystyrene and / or 0.1 to 3 wt. % of polyamide;
[0059] (f) 0.1 to 10 wt. %, preferably 0.1 to 5 wt. %, more preferably 0.1 to 3 wt. % of other components selected from talc, chalk, carbon, calcium stearate, titanium dioxide, pigments, metals, glass, paper, wood and combinations thereof, measured as described below.
[0060] Preferably, the post-consumer recycled polyolefin composition comprises at least limonene in an amount of at least 0.1 ppm.
[0061] Preferably components a), b) and at least one of c) to e), preferably c) together account for up to 100 wt% of the post-consumer recycled polyolefin composition.
[0062] The post-consumer recycled polyolefin composition may also comprise a residual ash content measured according to ISO 3451-1 (1997) standard of less than 3.0 wt%, preferably in the range of 0.5 to 2.7 wt%, more preferably 0.7 to 2.5 wt%.
[0063] The process of the present invention is able to tolerate the specified amounts of the listed components, and the modified polyolefin composition obtained by the process is of excellent quality for further reuse.
[0064] According to the present invention, the post-consumer recycled polyolefin composition has a melt flow rate MFR measured according to ISO 1133 at 2.16 kg load, 230° C. in the range of 1.0 to 100 g / 10 min, preferably in the range of 2.0 to 80 g / 10 min, more preferably in the range of 3.0 to 60 g / 10 min. 2 (1) (i.e., the initial melt flow rate at the beginning of the process).
[0065] The process of the present invention reduces the melt flow rate of post-consumer recycled polyolefin compositions and makes the resulting modified polyolefin compositions very convenient to process and suitable for reuse in various polyolefin applications due to enhanced mechanical stability.
[0066] Preferably, the modified polyolefin composition has a second melt flow rate MFR measured according to ISO 1133 at 2.16 kg load, 230° C. in the range of 0.1 to 50 g / 10 min, more preferably 0.1 to 40 g / 10 min, most preferably 0.1 to 30 g / 10 min. 2 (2) (i.e., the final melt flow rate after applying the method).
[0067] MFR 2 (2):MFR 2 The ratio of (1) is 1.00 or less, preferably 0.90 or less. More preferably, MFR 2 (2):MFR 2 The ratio of (1) is in the range of 0.01 to 0.95, more preferably in the range of 0.01 to 0.90.
[0068] The polyolefin composition recovered after consumption can usually exist in the form of particles, which are not limited by their geometric shape, as long as they include enough surface for the reaction in steps (B) and (C). However, preferably, the polyolefin composition recovered after consumption exists in the form of pellets, and its median thickness T50 measured by direct caliper measurement is in the range of 0.5 to 5.0 mm, preferably in the range of 0.8 to 3.5 mm. Pellets are preferably cylindrical or lens-shaped, and their median diameter D50 measured by optical analysis using a high-speed camera is in the range of 2.0 to 5.0 mm, preferably in the range of 2.5 to 4.5 mm.
[0069] The polyolefin composition of post-consumer recycling required by the present invention can be prepared by a pre-composition based on post-consumer recycling materials with other contents or forms. For example, post-consumer polymer waste can be processed by different mechanical (e.g., sorting) methods, washing or chemical (e.g., dissolving) methods to provide a polyolefin composition of post-consumer recycling for use in the method of the present invention.
[0070] Specifically, the post-consumer recycled polyolefin composition can be provided in a desired size and form by extruding in a single screw or twin screw extruder, preferably a co-rotating twin screw extruder, at 180 to 300° C., preferably 200 to 280° C., followed by a suitable pelletizing process (wherein the thickness and diameter of the pellets are defined). Suitable pelletizing processes include underwater pelletizing, water ring pelletizing, and strand pelletizing, the latter comprising solidifying one or more melt strands in a water bath and then cutting the strands into pellets. In all cases, the particle diameter is defined by the die diameter and the particle length is defined by the cutting frequency used in pelletizing.
[0071] Generally speaking, providing the polyolefin composition of post-consumption recovery in step (A) means that the composition is available. The polyolefin composition of post-consumption recovery can be provided by placing the composition in a reactor, wherein other components are added. However, the composition can also be added to the reactor when adding step (B).
[0072] Free Radical Initiators
[0073] In step (B) of the process of the present invention, 0.10 to 1.50 wt%, preferably 0.15 to 1.20 wt%, more preferably 0.20 to 1.00 wt% of a free radical initiator, based on the total weight of the post-consumer recycled polyolefin composition, is added to the post-consumer recycled polyolefin composition, and optionally, the components are mixed to form a mixture (1).
[0074] The free radical initiator can be selected from any free radical initiator suitable for the visbreaking reaction in the propylene polymer. Preferably, the free radical initiator is a carbon-carbon free radical compound, an azo compound, a stable nitroxyl compound, a sterically hindered NO-acyl compound or a peroxide compound. The peroxide compound is preferably selected from acyl peroxides, alkyl peroxides, hydroperoxides, peresters, peroxycarbonates and combinations thereof.
[0075] In a preferred embodiment, the free radical initiator is tert-butyl peroxyisopropyl carbonate.
[0076] The free radical initiator is preferably added to the post consumer recycled polyolefin composition as a liquid. Since most free radical initiators are solid compounds, they can be dissolved in a liquid prior to addition.
[0077] After adding the free radical initiator to the post-consumer recycled polyolefin composition, the components are preferably mixed to form a mixture (1), and preferably contacted for a period of at least 2 minutes, preferably 5 minutes to 30 minutes, more preferably 8 to 20 minutes, so as to achieve a relatively uniform absorption of the free radical initiator by the post-consumer recycled polyolefin composition.
[0078] In a preferred embodiment, the addition of step (B) is carried out in a flow-through reactor, such as a horizontal mixer with a paddle stirrer, preferably in a continuous mode. The post-consumer recycled polyolefin and the free radical initiator can be added to the flow-through reactor in the form of parallel streams. Preferably, the flow-through reactor is a horizontal flow-through reactor, and the components can be transported through the reactor by a transport paddle. In this way, a very effective absorption of the free radical initiator by the post-consumer recycled polyolefin is achieved.
[0079] However, alternatively, other reactors may be used in which, for example, the free radical initiator is added to the reactor after the post-consumer recycled polyolefin composition is placed in the reactor.
[0080] Step (B) is preferably carried out at a temperature in the range of 20 to 90° C., more preferably 40 to 80° C. Importantly, the process does not involve visbreaking, ie reacting any intermediates with a free radical initiator in the absence of a doubly unsaturated hydrocarbon compound.
[0081] Step (C) is preferably carried out after step (B). However, in one embodiment, steps (B) and (C) are carried out simultaneously by adding the free radical initiator and the di-unsaturated hydrocarbon compound simultaneously (e.g. in a masterbatch). In this embodiment, only one mixture (mixture (2)) is formed.
[0082] Diunsaturated hydrocarbon compounds
[0083] In step (C) of the process of the present invention, 0.05 to 0.50 wt. %, preferably 0.08 to 0.45 wt. %, more preferably 0.10 to 0.40 wt. % of a diunsaturated hydrocarbon compound having the general formula (1) is added, based on the total weight of the post-consumer recycled polyolefin composition:
[0084] (1)CH 2 =CH-(R)-CH=CH 2 ,
[0085] wherein R may be present or absent, and if present, R is an aliphatic or aromatic hydrocarbon group containing 1 to 6 carbon atoms, and the components are mixed to form a mixture (2).
[0086] Formula (1) includes formula (1a) and formula (1b):
[0087] (1a)CH 2 =CH-CH=CH 2
[0088] (1b)CH 2 =CH-R-CH=CH 2 ,
[0089] wherein R in formula (1b) is an aliphatic or aromatic hydrocarbon group containing 1 to 6 carbon atoms.
[0090] In a preferred embodiment, the di-unsaturated hydrocarbon compound of formula (1) is 1,3-butadiene (ie, R does not exist in formula (1)).
[0091] In other embodiments, the residue R in the diunsaturated hydrocarbon compound of formula (1) is selected from methylene, ethylene, propylene, n-butylene, tert-butylene, n-pentylene, isopentylene, tert-pentylene, n-hexylene, tert-hexylene, isohexylene, neohexylene and phenylene.
[0092] Preferably, the di-unsaturated hydrocarbon compound can be added in its natural aggregate state at the addition temperature. Preferably, the di-unsaturated hydrocarbon compound is added in gaseous form.
[0093] The components are mixed to achieve good absorption of unsaturated hydrocarbon compounds and free radical initiators by the polyolefin composition recovered after consumption. Mixing can be carried out in any type of reactor, preferably in any reactor suitable for solid-gas reaction. Mixing time is preferably in the range of 1 second to 30 minutes, more preferably in the range of 2 seconds to 5 minutes.
[0094] In a preferred embodiment, the reactor is a vertical flow-through reactor in which particles of the polyolefin composition recovered after consumption are conveyed by gravity. Unsaturated hydrocarbon compounds are added to the reactor as a stream and the polyolefin composition recovered after consumption is mixed during the falling motion in the unsaturated hydrocarbon compound stream.
[0095] Step (C) is preferably carried out at a temperature ranging from 20°C to 90°C, more preferably from 40°C to 80°C.
[0096] Step (D) is performed after step (C).
[0097] In step (D) of the process of the present invention, a mixture (2) comprising a post-consumer recycled polyolefin composition, a free radical initiator and a di-unsaturated hydrocarbon compound is extruded at a temperature ranging from 180 to 300° C., preferably from 200 to 280° C., to obtain a modified polyolefin composition.
[0098] Extrusion can be carried out in any conventional manner known in the art. Preferably, extrusion is carried out in a continuous melt mixing device such as a single screw extruder, a co-rotating twin screw extruder or a co-kneader. The barrel temperature is preferably 200 to 280° C. The screw speed of the melt mixing device is preferably adjusted to a range of 100 to 750 rpm.
[0099] More preferably, the melt mixing device comprises a feed zone, a kneading zone and a die zone, and a specific temperature profile is maintained along the screw of the melt mixing device, with an initial temperature T1 in the feed zone, a maximum temperature T2 in the kneading zone and a final temperature T3 in the die zone, all of which are defined as barrel temperatures. The barrel temperature T1 (in the feed zone) is preferably in the range of 180 to 260° C. The barrel temperature T2 (in the kneading zone) is preferably in the range of 260 to 300° C. The barrel temperature T3 (in the die zone) is preferably in the range of 220 to 280° C.
[0100] In a preferred embodiment, the process of the present invention is carried out as a continuous process using the above-mentioned flow-through reactor and the mixture (2) prepared in step (C) is directly fed to an extruder to prepare the modified polyolefin composition.
[0101] After step (D), the modified polyolefin composition is preferably pelletized in an underwater pelletizer or after solidification of one or more strands by a suitable pelletizing method. Suitable pelletizing methods include underwater pelletizing, water ring pelletizing and strand pelletizing, the latter comprising solidifying one or more melt strands in a water bath and then cutting the strands into pellets.
[0102] Having a low content of crosslinked or gel-like fraction, usually represented by the xylene heat insoluble (XHU) fraction, is advantageous for many applications, in particular films or coatings, where a low xylene heat insoluble (XHU) fraction enables a good surface quality to be achieved. The process of the present invention is preferably characterized by providing a ratio of the amount of the xylene heat insoluble (XHU) fraction of the modified polyolefin composition to the amount of the xylene heat insoluble (XHU) fraction of the post-consumer recycled polyolefin composition, determined according to EN 579, which is below 2.5, preferably in the range of 0.1 to 2.4, more preferably in the range of 0.2 to 2.3.
[0103] Having a relatively high crystallization temperature Tc is advantageous for many conversion processes, in particular injection molding and blow molding, where a high crystallization temperature Tc allows to reduce the cycle time. The process of the present invention is preferably characterized by increasing the crystallization temperature Tc of the propylene polymer content in the polyolefin. Preferably, the difference between the crystallization temperature Tc of the propylene polymer content of the modified polyolefin composition determined according to ISO 11357-3 and the crystallization temperature Tc of the post-consumer recycled polyolefin composition is greater than 0°C, preferably in the range of 1 to 10°C, more preferably in the range of 1.5 to 6°C.
[0104] Other additives
[0105] In the process of this method, other additives can be added to the mixture. Especially, conventional additives for the polyolefin preparation process can be added, such as modifiers, stabilizers, antistatic agents, lubricants, nucleators, foam nucleators, acid scavengers, UV stabilizers, slip agents and pigments, as well as fillers and reinforcing agents. The advantage of the polyolefin composition recovered after consumption is that it usually contains additives from the preparation process of the original polymer and the first use of the article, which means that further addition of additives may not be required at all. However, if particularly stabilizers such as primary antioxidants and auxiliary antioxidants have been consumed in the processing and use stage, it is preferred to add an amount of stabilizer.
[0106] Modified polyolefin composition
[0107] The present invention also relates to a modified polyolefin composition obtainable by the process of the present invention in any of the above-mentioned embodiments.
[0108] By controlled introduction of long chain branching by the method of the present invention, the performance of the modified polyolefin composition has changed. The polyolefin composition recovered after consumption with different propylene polymers and ethylene polymer ratios has obtained excellent results in processability and further application selection. This is unexpected because the reaction with the free radical initiator causes different mechanisms of action in propylene polymers and ethylene polymers. Visbreaking occurs in propylene polymers, while ethylene polymers usually form a highly crosslinked structure when reacting with the free radical initiator.
[0109] The process of the present invention converts this problem into a potential advantage by combining chain scission in the propylene polymer with branching and crosslinking reactions in the ethylene polymer and involving some crosslinking polymer reactions leading to improved compatibility.
[0110] The modified polyolefin composition is preferably characterized by a second melt flow rate MFR measured according to ISO 1133 at 230°C under a load of 2.16 kg 2 (2) (i.e. the final melt flow rate after applying the method) is in the range of 0.1 to 50 g / 10 min, more preferably 0.1 to 40 g / 10 min, most preferably 0.1 to 30 g / 10 min.
[0111] Another way to characterize the structure of branched polypropylene is the Rheotens measurement. As the shear force applied to the polymer (e.g. during melt extrusion) increases, branched polypropylene exhibits higher melt strength. This property is known as strain hardening. In the Rheotens test, the shear strength of the branched polypropylene is measured by a Rheotens device (Gottfork). The strain hardening behavior of polymers is analyzed by the product of ELECTRONICS, Siemensstr. 2, 74711 Buchen, Germany, where the melt strand is elongated by pulling it down at a defined acceleration. The pulling force F is recorded as a function of the pulling speed v. The test process is carried out at a temperature of 23° C. More details are given in the experimental section.
[0112] The modified polyolefin composition is preferably characterized by a F measured according to the Rheotens method of ISO 16790:2005. 30 The melt strength is from 3.5 to 30.0 cN, more preferably from 4.0 to 25.0 cN, most preferably from 4.5 to 22.0 cN.
[0113] The modified polyolefin composition is preferably characterized by a v measured according to the Rheotens method of ISO 16790:2005. 30 The melt stretchability is in the range of 150 to 300 mm / s, more preferably 155 to 290 mm / s and most preferably 160 to 280 mm / s.
[0114] Since the parameter F 30 Melt strength and v 30 Melt extensibility depends on the melt flow rate, and thus the modified polyolefin composition is preferably characterized by a value of at least 0.5 cN·10 min / g, more preferably at least 2.0 cN·10 min / g, and / or a F in the range of 0.5 to 80.0 cN·10 min / g, more preferably 2.0 to 80.0 cN·10 min / g. 30 / MFR 2 (2) value; and / or a v of at least 20 mm·600 / g, more preferably 50 mm·600 / g 30 / MFR 2 (2) value, and / or v in the range of 20 to 1200 mm·600 / g, more preferably 50 to 1200 mm·600 / g 30 / MFR 2 (2)Value.
[0115] The modified polyolefin composition is preferably characterized in that the amount of xylene heat insoluble (XHU) fraction determined according to EN 579 is in the range of 0.0 to 3.5 wt.-%, more preferably 0.1 to 3.0 wt.-% and most preferably 0.1 to 2.5 wt.-%, based on the total weight of the modified polyolefin composition.
[0116] The modified polyolefin composition is preferably characterized by a broad molecular weight distribution (MWD), which is determined according to the GPC method and represented by the ratio between the weight average molecular weight (Mw) and the number average molecular weight (Mn). The Mw / Mn ratio, also called polydispersity, is in the range of 5 to 15, more preferably 6 to 14, most preferably 7 to 13. The Mw / Mn ratio of the modified polyolefin composition is preferably higher than the Mw / Mn of the PCR polyolefin composition.
[0117] The modified polyolefin composition is preferably characterized by: -1 The strain hardening factor (SHF) measured at a strain rate of 2.0 to 20.0, more preferably 2.2 to 15.0, most preferably 2.3 to 12.5, and at 180°C.
[0118] Due to its dependence on melt flow rate, the strain hardening factor can be defined as SHF / MFR 2 Therefore, the modified polyolefin composition is preferably characterized by at least 0.5 (g / 10min) -1 , more preferably at least 1.2 (g / 10min) -1 SHF / MFR 2 (2) value, and / or 0.5 to 40.0 (g / 10min) -1 , more preferably 1.2 to 30.0 (g / 10min) -1 SHF / MFR in the range 2 (2)Value.
[0119] Uses and products
[0120] The present invention also relates to the use of the modified polyolefin composition in any of the above embodiments and prepared by the method of the present invention in the manufacture of articles, and the articles.
[0121] The article is preferably a foamed article, a film or an extrusion coating. In a preferred embodiment, the article is a foamed article, a film or an extrusion coating and comprises greater than 50 wt%, preferably greater than 75 wt%, such as 90 wt% of the modified polyolefin composition based on the total weight of the article.
[0122] In a particularly preferred embodiment, the article is a foamed article comprising more than 50 wt%, preferably more than 75 wt%, for example 90 wt% of the modified polyolefin composition, based on the total weight of the modified polyolefin composition, and the MFR of the modified polyolefin composition measured according to ISO 1133 at 2.16 kg load and 230°C is 2 0.1 to 1.5 g / 10 min.
[0123] In another particularly preferred embodiment, the article is a film or an extrusion coating, preferably for a substrate such as paper, metal, textile or nonwoven, comprising more than 50 wt%, preferably more than 75 wt%, for example 90 wt%, based on the total weight of the film or extrusion coating, respectively, of the modified polyolefin composition, and the modified polyolefin composition has an MFR in the range of 1.5 to 10.0 g / 10 min, measured at 230° C. under a load of 2.16 kg according to ISO 1133. 2 .
[0124] Example
[0125] Measurement method
[0126] Unless defined otherwise, the following definitions of terms and assay methods apply to the above general description of the invention as well as to the following examples.
[0127] Melt flow rate
[0128] The melt flow rate (MFR) is determined according to ISO 1133 and is expressed in g / 10 min. The MFR is an indicator of the flowability of the polymer and thus of the processability. The higher the melt flow rate, the lower the viscosity of the polymer. Here, the MFR 2 It was measured at a temperature of 230°C and a load of 2.16 kg.
[0129] F 30 Melt strength and v 30 Melt stretchability
[0130] The test described herein follows ISO 16790:2005. The strain hardening behavior is measured by the method described in the paper "Rheotens-Mastercurves and Drawability of Polymer Melts", MH Wagner, Polymer Engineering and Science, Vol. 36, pp. 925 to 935. The strain hardening behavior of polymers is analyzed with a Rheotens device (product of Gottfert, Siemensstr. 2, 74711 Buchen, Germany), wherein the melt strands are elongated by pulling down with a specified acceleration. The Rheotens experiment simulates industrial spinning and extrusion processes. In principle, the melt is pressed or extruded through a circular die, and then the resulting strands are pulled out. The stress on the extrudate is recorded as a function of melt properties and measurement parameters (particularly the ratio between output and traction speed, which is actually a measure of the elongation).
[0131] For the results given below, the material was extruded using a laboratory extruder HAAKE Polylab system and a gear pump with a cylindrical die (L / D = 6.0 / 2.0 mm). The gear pump was pre-adjusted to a strand extrusion rate of 5 mm / s and the melt temperature was set to 200°C. The length of the rotating line between the die and the Rheotens wheel was 80 mm. At the start of the experiment, the winding speed of the Rheotens wheel was adjusted to the speed at which the polymer strand is extruded (tensile force is zero). The experiment was then started by slowly increasing the winding speed of the Rheotens wheel until the polymer filament breaks. The acceleration of the wheel is small enough so that the tensile force can be measured under quasi-steady-state conditions. The acceleration of the melt strand pulled down is 120 mm / s 2 Rheotens is run in conjunction with the PC program EXTENS. This is a real-time data acquisition program that displays and stores the measured data of the pulling force and the pull-down speed. The end point of the Rheotens curve (force vs. pulley speed) is considered to be F 30 Melt strength and elongation values.
[0132] Strain Hardening Factor (SHF)
[0133] The strain hardening factor is defined as
[0134]
[0135] in
[0136] is the uniaxial extensional viscosity; and In the linear deformation range it is three times higher than the time-dependent shear viscosity.
[0137] Determination of the linear viscoelastic envelope in tension using IRIS Rheo Hub 2008 requires calculation of discrete relaxation time spectra from the storage and loss modulus data (G', G" (ω)). The linear viscoelastic data (G', G" (ω)) were obtained by frequency sweep measurements at 180°C on an Anton Paar MCR 300 equipped with 25 mm parallel plates. The basic calculation principle for determining the discrete relaxation spectrum is described in M, Winter HH, "Determination of the discrete relaxation and retardation time spectra from dynamic mechanical data", Rheol. Acta 28: 511519 (1989). IRIS RheoHub 2008 represents the relaxation time spectrum as the sum of N Maxwell modes
[0138]
[0139] where g i and λ i is the material parameter, G e is the equilibrium modulus.
[0140] The maximum number of modes N used to determine the discrete relaxation spectrum was selected by using the "optimum" option in IRIS RheoHub 2008. The equilibrium modulus G e Set to zero. Used to get The nonlinear fitting was performed using the Doi-Edwards model in IRIS RheoHub 2008.
[0141] Uniaxial extension viscosity The results are obtained by uniaxial extensional flow measurement on an Anton Paar MCR 501 equipped with a Sentmanat tensile fixture (SER-1). The temperature of the uniaxial extensional flow measurement was set at 180 °C and a flow rate of 0.3 s was applied. -1 Up to 10s -1 Stretching (strain) rate within the range and covers a range of Hencky strains
[0142] ε=ln[(l–l 0 ) / l 0 ],
[0143] Among them l 0 is the original length, l is the actual sample fixed length, ranging from 0.3 to 3.0. Special care should be taken for the preparation of the extensional flow samples. The samples are prepared by compression molding at 230°C and then slowly cooled to room temperature (without forced water cooling or air cooling). This procedure allows to obtain samples with good shape and no residual stress. Before the uniaxial extensional flow measurement, the sample is placed at the test temperature for a few minutes to ensure thermal stability (set temperature ± 0.1°C).
[0144] Strain hardening factor (SHF) at 180℃ and strain rate 1s -1 and the Hencky strain was 2.5.
[0145] XHU fraction
[0146] The xylene heat insoluble fraction (XHU) was determined according to EN 579. Approximately 2.0 g of polymer (m p ) and put it into the weighing metal net, the total weight is (m p+m). The polymer in the net was extracted with boiling xylene in a Soxhlet apparatus for 5 hours. The eluent was then replaced with fresh xylene and boiling was continued for one hour. The net was then dried and weighed again (m XHU+m ). XHU+m -m m =m XHU The mass of xylene heat insoluble matter obtained (m XHU ) and the weight of the polymer (m p ) to obtain the fraction m of xylene insoluble matter XHU / m p .
[0147] Pellet size
[0148] The average pellet size of the PCR polyolefin composition was determined by two methods applied to thickness and diameter, respectively. The median pellet thickness T50 was calculated by manually measuring the thickness of 10 pellets using a standardized caliper. The median pellet diameter D50 was determined by optical measurement of the pellets using a high-speed CCD camera, model PS25C, from OCS GmbH, Germany.
[0149] Isotacticity and comonomer content of polypropylene
[0150] Quantitative nuclear magnetic resonance (NMR) spectroscopy is used to quantify the isotacticity and comonomer content of the propylene (co)polymer components.
[0151] Use for 1 H and 13 Quantitative measurements were recorded in solution on a Bruker Advance III500 NMR spectrometer operating at 400.15 and 100.62 MHz, respectively. 13 C{ 1 H}NMR spectroscopy. 13 All spectra were recorded at 125 °C with a C-optimized 10 mm extended temperature probe head and nitrogen was used for all pneumatics.
[0152] About 200 mg of the material was dissolved in 1,2-tetrachloroethane-d 2 (TCE-d 2). To ensure a homogeneous solution, after preliminary sample preparation in a heat block, the NMR tube was further heated in a rotary oven for at least 1 hour. After insertion of the magnet, the tube was rotated at a frequency of 10 Hz. This setup was chosen primarily for the high resolution required for quantification of stereoregularity distribution (Busico, V., Cipullo, R., Prog. Polym. Sci. 26 (2001) 443; Busico, V.; Cipullo, R., Monaco, G., Vacatello, M., Segre, AL, Macromolecules 30 (1997) 6251). Standard single pulse excitation was used using NOE and a two-level WALTZ16 decoupling scheme (Zhou, Z., Kuemmerle, R., Qiu, X., Redwine, D., Cong, R., Taha, A., Baugh, D. Winniford, B., J. Mag. Reson. 187 (2007) 225; Busico, V., Carbonniere, P., Cipullo, R., Pellecchia, R., Severn, J., Talarico, G., Macromol. Rapid Commun. 2007, 28, 11289). A total of 8192 (8k) transients were obtained for each spectrum.
[0153] A proprietary computer program was used to quantify 13 C{ 1 H} NMR spectra are processed, integrated and relevant quantitative properties are determined from the integration.
[0154] All chemical shifts were internally referenced to the methyl isotactic pentad (mmmm) at 21.85 ppm.
[0155] Characteristic signals corresponding to regio defects (Resconi, L., Cavallo, L., Fait, A., Piemontesi, F., Chem. Rev. 2000, 100, 1253; Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157; Cheng, HN, Macromolecules 17 (1984), 1950) or comonomers were observed.
[0156] The stereoregularity distribution is quantified by integrating the methyl region between 23.6-19.7 ppm, correcting for any sites not associated with the stereo sequence of interest (Busico, V., Cipullo, R., Prog. Polym. Sci. 26 (2001) 443; Busico, V., Cipullo, R., Monaco, G., Vacatello, M., Segre, AL, Macromolecules 30 (1997) 6251).
[0157] Specifically, the effects of regio defects and comonomers on the quantification of the tacticity distribution are corrected by subtracting representative regio defect and comonomer integrals from the specific integrated region of the stereo sequence.
[0158] Isotacticity is determined at the pentad level and is reported as the percentage of isotactic pentad (mmmm) sequences relative to all pentad sequences:
[0159] [mmmm]% = 100*(mmmm / sum of all quintuples)
[0160] Using the method of Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157), by integrating 13 C{ 1 The comonomer fraction is quantified by integrating multiple signals across the spectral region in the H} spectrum. This approach was chosen for its robust nature and ability to account for the presence of regio defects when required. The integration region was slightly adjusted to improve applicability over the entire range of comonomer contents encountered.
[0161] For systems where only isolated ethylene in PPEPP sequences is observed, the method of Wang et al. is modified to reduce the effect of non-zero integrals at sites known to be absent. This approach reduces the overestimation of ethylene content in such systems and does so by reducing the number of sites used to determine absolute ethylene content:
[0162] E=0.5(S ββ +S βγ +S βδ +0.5(S αβ +S αγ ))
[0163] By using this set of sites, using the same notation used in the paper by Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157), the corresponding integral equation becomes:
[0164] E=0.5(I H +I G +0.5(I C +I D ))
[0165] The equation for absolute propylene content was not modified.
[0166] The mole percentage of comonomer incorporation is calculated from the mole fraction:
[0167] E[mol%]=100*f E
[0168] The weight percent of comonomer incorporation is calculated from the mole fraction:
[0169] E[wt%]=100*(f E *28.06) / ((f E *28.06)+((1-f E )*42.08))
[0170] Molecular weight average, molecular weight distribution
[0171] The molar mass averages (Mw and Mn) and the polydispersity Mw / Mn are determined by gel permeation chromatography (GPC) according to ISO 16014-4:2003 and ASTM D 6474-99 using the following formula:
[0172]
[0173] Among them A i and M i are the chromatographic peak slice area and the molecular weight (MW) of the polyolefin.
[0174] A PolymerCharGPC instrument equipped with an infrared (IR) detector and 3x Olexis and 1x Olexis Guard columns from Polymer Laboratories were used at 160°C and a constant flow rate of 1 mL / min, with 1,2,4-trichlorobenzene (TCB, stabilized with 250 mg / L 2,6-di-tert-butyl-4-methylphenol) as solvent. 200 μL of sample solution was injected for each analysis. The column set was calibrated using universal calibration (according to ISO 16014-2:2003) using at least 15 narrow MWD polystyrene (PS) standards ranging from 0.5 kg / mol to 11500 kg / mol. The Mark Houwink constants for PS, PE and PP are as described in ASTM D 6474-99. All samples were prepared by dissolving 5.0 to 9.0 mg of polymer in 8 mL (at 160°C) stabilized TCB (same as mobile phase) in the autosampler of the GPC instrument at 160°C with continuous gentle shaking for 2.5 hours.
[0175] Crystex analysis, crystalline fraction (CF) and soluble fraction (SF)
[0176] The crystalline fraction (CF) and soluble fraction (SF) of the PCR polyolefin composition as well as the ethylene content and intrinsic viscosity of each fraction were analyzed using a CRYSTEX instrument from Polymer Char (Valencia, Spain) according to Annex B of ISO 6427. Detailed information on this technology and method can be found in the literature (Ljiljana Jeremic, Andreas Albrecht, Martina Sandholzer & Markus Gahleitner (2020) Rapid characterization of high-impact ethylene–propylene copolymer composition by crystallization extraction separation: comparability to standard separation methods, International Journal of Polymer Analysis and Characterization, 25: 8, 581-596).
[0177] The crystalline and amorphous fractions were separated by temperature cycles of dissolution at 160° C., crystallization at 40° C. and redissolution in 1,2,4-trichlorobenzene at 160° C. Quantification of SF and CF as well as determination of the ethylene content (C2) were achieved by an integrating infrared detector (IR4) and the intrinsic viscosity (IV) was determined using an online 2-capillary viscometer.
[0178] The IR4 detector is a multi-wavelength detector that measures two different wavelength bands (CH 3 Stretching vibration (centered at about 2960cm -1 ) and CH stretching vibration (2700-3000cm -1 ) is used to determine the concentration and ethylene content in ethylene propylene copolymers. The IR4 detector uses 8 known ethylene contents ranging from 2 wt % to 69 wt % (by 13 C-NMR measurement) and each EP copolymer series at different concentrations in the range of 2 to 13 mg / ml was calibrated. In order to simultaneously meet the characteristics, concentration and ethylene content of various polymer concentrations expected during Crystex analysis, the following calibration equation was applied:
[0179] Conc=a+b*Abs(CH)+c*(Abs(CH))2+d*Abs(CH 3 )+e*(Abs(CH 3 )2+
[0180] f*Abs(CH)*Abs(CH3)
[0181] CH 3 / 1000C=a+b*Abs(CH)+c*Abs(CH 3 )+d*(Abs(CH 3 ) / Abs(CH))+e*
[0182] (Abs(CH 3 ) / Abs(CH))2
[0183] Constants a to e of Equation 1 and constants a to f of Equation 2 are determined by using least squares regression analysis.
[0184] Use the following relationship to convert CH 3 / 1000C converted to ethylene content (in weight %):
[0185] Weight % (ethylene in EP copolymer) = 100-CH 3 / 1000TC*0.3
[0186] The intrinsic viscosity (IV) of the PCR polyolefin composition and its soluble fraction and crystalline fraction were determined using an online 2-capillary viscometer and correlated with the corresponding IV determined by the standard method in decalin according to ISO 1628-3. Calibration was performed using various EP PP copolymers with IV = 2-4 dL / g. The calibration curve determined was linear:
[0187] IV(dL / g)=a*Vsp / c
[0188] The sample to be analyzed is weighed at a concentration of 10 mg / ml to 20 mg / ml. To avoid injection of possible gels and / or polymers (such as PET and PA) that are not soluble in TCB at 160°C, the weighed sample is loaded into a stainless steel mesh MW 0,077 / D0,05 mm.
[0189] After automatically filling the vial with 1,2,4-TCB containing 250 mg / l 2,6-tert-butyl-4-methylphenol (BHT) as an antioxidant, the sample was dissolved at 160°C until completely dissolved, typically 60 minutes, with constant stirring at 400 rpm. To avoid sample degradation, the polymer solution was blanketed with nitrogen during the dissolution process.
[0190] A specified volume of sample solution is injected into a column filled with an inert carrier, where crystallization of the sample and separation of the soluble fraction from the crystalline fraction occurs. This process is repeated twice. During the first injection, the entire sample is measured at high temperature to determine the IV [dl / g] and C of the PP composition. 2 [wt%] During the second injection, the soluble fraction (at low temperature) and the crystalline fraction (at high temperature) in the crystallization cycle were measured (wt% SF, wt% C 2 , IV).
[0191] DSC analysis, crystallization temperature (Tc) and crystallinity
[0192] Use differential scanning calorimetry (DSC) to measure the crystallinity of ethylene polymers and the crystallization temperature Tc of polyolefin compositions. Use TA Instrument Q200 differential scanning calorimetry (DSC) to measure DSC parameters for 5 to 7 mg samples. DSC is operated in a heating / cooling / heating cycle according to ISO 11357 / Part 3 / Method C2, with a scanning rate of 10°C / min and a temperature range of -30 to +225°C. The crystallization temperature (Tc) is determined by the cooling step, while the melting temperature (Tm) and the melting enthalpy (Hm) are determined by the second heating step. The crystallinity is calculated from the melting enthalpy by assuming that the Hm value of completely crystalline polypropylene is 209J / g and that of completely crystalline polyethylene is 293J / g (see Brandrup, J., Immergut, EH, Eds. Polymer Handbook, 3rd ed. Wiley, New York, 1989; Chapter 3).
[0193] PCR polyolefin composition: amount of propylene (co)polymer, ethylene (co)polymer, polystyrene and polyamide-6
[0194] To establish different calibration curves and different standards, a first iPP and HDPE as well as a second iPP, PS and PA6 were mixed in relevant fractions. To quantify the content of foreign polymers, solid-state IR spectra were recorded using a Bruker Vertex 70 FTIR spectrometer. The films were prepared using a compression molding apparatus at 190 °C and 4-6 MPa clamping force. The thickness of the films for the calibration standards for iPP and HDPE was 300 μm and for the quantification of iPP, PS and PA6 was 50-100 μm. Standard transmission FTIR spectroscopy was used with a spectral range of 4000-400 cm -1 , aperture is 6mm, spectral resolution is 2cm -1 , 16 background scans, 16 spectral scans, an interferogram zero fill factor of 32, and Norton Beer strong apodization.
[0195] Measured 1167cm in iPP -1 The absorbance of the band at 140 nm was measured and the iPP content was quantified according to a calibration curve (absorption / thickness (in cm) vs. iPP content (in wt%)).
[0196] Measurements 1601cm -1 (PS) and 3300cm -1The absorbance of the band at (PA6) was determined and the PS and PA6 contents were quantified according to a calibration curve (absorption / thickness in cm vs. PS and PA content in wt. %). The content of polyethylene and ethylene-containing copolymers was obtained by subtracting (iPP+PS+PA6) from 100, taking into account the content of non-polymer impurities determined as follows. The analysis was performed in duplicate.
[0197] PCR polyolefin composition: talc and chalk content
[0198] Thermogravimetric analysis (TGA) experiments were performed using a Perkin Elmer TGA8000 according to ISO 3451-1 (1997). Approximately 10-20 mg of material was placed in a platinum pan. The temperature was equilibrated at 50°C for 10 minutes and then raised to 950°C at a heating rate of 20°C / min under nitrogen. Approximately 550°C and 700°C (WCO 2 ) is attributed to the weight loss from CaCO 3 Evolved CO 2 , so the chalk content is estimated as follows:
[0199] Chalk content = 100 / 44 x WCO 2
[0200] The temperature was then lowered to 300°C at a cooling rate of 20°C / min. The gas was then switched to oxygen and the temperature was raised again to 900°C. The weight loss in this step is attributed to carbon black (Wcb). Knowing the contents of carbon black and chalk, the ash content excluding chalk and carbon black was calculated as follows:
[0201] Ash content = (ash residue) – 56 / 44 x WCO 2 –Wcb
[0202] The ash content is the weight % measured at 900°C in the first step carried out under nitrogen. The ash content is estimated to be the same as the talc content of the recyclate studied.
[0203] PCR Polyolefin Composition: Metal Amount
[0204] The amount of metal was determined by X-ray fluorescence (XRF).
[0205] PCR polyolefin composition: amount of paper and wood
[0206] The content of paper and wood was determined by conventional laboratory methods including grinding, flotation, microscopy and thermogravimetric analysis (TGA).
[0207] PCR Polyolefin Composition: Limonene Measurement
[0208] Limonene quantification was performed by standard addition using solid phase microextraction (HS-SPME-GC-MS).
[0209] 50mg of ground sample was weighed into a 20mL headspace vial and different concentrations of limonene and a glass coated magnetic stir bar were added. The vial was closed with a magnetic cap lined with silicone / PTFE. Diluted limonene standards of known concentrations were added to the sample using a microcapillary (10pL). 0, 2, 20 and 100ng were added to equal 0mg / kg, 0.1mg / kg, 1mg / kg and 5mg / kg limonene, and additional standard amounts of 6.6mg / kg, 11mg / kg and 16.5mg / kg limonene were used in combination with some of the samples tested in this application. For quantification, ions 93 collected in SIM mode were used. Volatile components were enriched by headspace solid phase microextraction at 60°C for 20 minutes using a 2cm stable curved 50 / 30pm DVB / Carboxen / PDMS fiber. Desorption was performed directly in the heated injection port of the GCMS system at 270°C.
[0210] GCMS parameters:
[0211] Chromatographic column: 30m HP 5MS 0.25*0.25
[0212] Injector: Splitless, with 0.75mm SPME liner, 270℃
[0213] Temperature program: -10℃(1min)
[0214] Carrier gas: Helium 5.0, linear velocity 31 cm / s, constant flow
[0215] MS: Single quadrupole, direct interface, 280°C interface temperature
[0216] Acquisition: SIM scan mode
[0217] Scan parameters: 20-300amu
[0218] SIM parameters: m / Z 93, 100 ms dwell time
[0219] PCR Polyolefin Composition: Total Free Fatty Acid Content
[0220] Fatty acid quantification was performed using headspace solid phase microextraction (HS-SPME-GC-MS) by standard addition.
[0221] 50 mg of ground sample was weighed in a 20 mL headspace vial and after adding different concentrations of limonene and a glass-coated magnetic stir bar, the vial was closed with a silicone / PTFE lined magnetic cap. Three different levels of known concentrations of a diluted free fatty acid mixture (acetic acid, propionic acid, butyric acid, valeric acid, hexanoic acid and octanoic acid) standard were added to the sample using a 10 μL microcapillary. The addition of 0, 50, 100 and 500 ng was equivalent to a concentration of 0 mg / kg, 1 mg / kg, 2 mg / kg and 10 mg / kg for each acid. For all acids except propionic acid, ion 60 acquired in SIM mode was used for quantification, and ion 74 was used for propionic acid.
[0222] GCMS parameters:
[0223] Chromatographic column: 20m ZB Wax plus 0.25*0.25
[0224] Injector: Split ratio 5:1, with glass-lined split liner, 250°C
[0225] Temperature program: 40℃(1min)@6℃ / min to 120℃, @15℃ to 245℃(5min)
[0226] Carrier gas: Helium 5.0, linear velocity 40cm / s, constant flow
[0227] MS: Single quadrupole, direct interface, 220°C interface temperature
[0228] Acquisition: SIM scan mode
[0229] Scan parameters: 46-250amu 6.6 scans / second
[0230] SIM parameters: m / z 60, 74, 6.6 scans / sec
[0231] experiment
[0232] Seven inventive examples (IE1 to IE7) and seven comparative examples (CE1 to CE7) were prepared, wherein comparative examples CE1 to CE4 contained neither a free radical initiator nor a di-unsaturated hydrocarbon compound, and comparative examples CE5 to CE7 contained only a free radical initiator and no di-unsaturated hydrocarbon compound. The properties of the PCR polyolefin compositions used are shown in Table 1 below.
[0233] Table 1 : Properties of PCR polyolefin compositions used in the examples.
[0234]
[0235]
[0236] *PCR mix = PCR2 / PCR1 1:1
[0237] All PCR polyolefin compositions contained more than 0.1 ppm limonene.
[0238] Preparation process:
[0239] Commercially available post-consumer recycled polyolefin compositions comprising propylene and ethylene polymers supplied by mtm Plastics, Germany, as shown in Table 1 below, were either used directly in the form of cylindrical pellets having a median thickness T50 of 3 mm and a median diameter D50 of 3.5 mm or were first subjected to an extrusion step in a Coperion ZSK32 co-rotating twin-screw extruder at 220°C and then to underwater pelletization in a Nordson-BKG unit with a 10-hole die of 2.8 mm diameter to form cylindrical pellets having a median thickness T50 of 1 mm and a median diameter D50 of 3.5 mm.
[0240] For all inventive examples, the pellets were mixed with a peroxide (POX) as a free radical initiator (Trigonox BPIC C75, obtained from Nouryon) in a horizontal mixer with a paddle stirrer at a temperature of 65°C, maintaining an average residence time of about 15. The mixture (1) was conveyed by paddles to a vertical reactor, where butadiene was added (<1 min residence time). The mixture (2) was transferred under an inert atmosphere to a Theyson TSK60 co-rotating twin-screw extruder with a barrel diameter of 60 mm and an L / D ratio of 48, equipped with a high-intensity mixing screw with three kneading zones and a two-step degassing device. The melt temperature profile was selected with an initial temperature T1=240°C in the feed zone, a maximum temperature T2=280°C in the last kneading zone, a final temperature T3=230°C in the die zone, all temperatures being defined as barrel temperatures. The screw speed was set at 300 to 480 rpm depending on the MFR. However, for comparative examples CE1 to CE5, the same process was used but without the addition of butadiene (CE5) or butadiene and POX (CE1 to CE4).
[0241] The resulting polymer melt was pelletized in a Gala AW6 underwater pelletizer with a 24-hole die of 2.4 mm diameter.
[0242] For comparative examples CE6 and CE7, the PCR polyolefin composition (cylindrical pellets with a median thickness T50 of 3 mm and a median diameter D50 of 3.5 mm) was dry blended with peroxide and directly subjected to the extrusion step in a Coperion ZSK18 co-rotating twin screw extruder using a temperature profile similar to that of the TSK 60. The resulting melt was solidified in a water bath into two strands, which were then pelletized.
[0243] All process conditions are summarized in Table 2 (Inventive Examples) and Table 3 (Comparative Examples).
[0244] Table 2: Process conditions - Inventive Examples.
[0245]
[0246]
[0247] *PCR mix = PCR2 / PCR1 1:1
[0248] Table 3: Process conditions - Comparative Examples.
[0249] Example CE1 CE2 CE3 CE4 CE5 CE6 CE7 PCR parameters PCR1 PCR Mix* PCR2 PCR3 PCR3 PCR3 PCR3 Pellet size, mm 3 1 3 1 1 3 3 POX, weight% 0 0 0 0 0.64 0.23 0.90 Butadiene (BD), weight % 0 0 0 0 0 0 0 POX / BD nd nd nd nd nd nd nd Extruder TSK60 TSK60 TSK60 TSK60 TSK60 ZSK18 ZSK18 Production capacity, kg / h 100 100 100 200 100 6 6 Screw speed, rpm 400 400 400 400 400 450 450 Torque, % 71 59 60 69 57 40 34
[0250] *PCR mix = PCR2 / PCR1 1:1
[0251] The properties of the produced modified polyolefin compositions were analyzed. The results are shown in Table 4 (Inventive Examples) and Table 5 (Comparative Examples).
[0252] Table 4: Parameters of modified polyolefin compositions - Inventive Examples.
[0253]
[0254]
[0255] *PCR mix = PCR2 / PCR1 1:1
[0256] Table 5: Parameters of modified polyolefin compositions - Comparative Examples.
[0257]
[0258]
[0259] *PCR mix = PCR2 / PCR1 1:1
[0260] The results show that, by the method of the present invention, the melt flow rate MFR of the polyolefin composition is 2 (2.16 kg load, 230 ° C) significantly reduced. In contrast, the addition of peroxide alone enhanced the MFR 2 (CE5 to CE7). As expected, in the absence of both components, the MFR 2 Remain unchanged (CE1 to CE4).
[0261] Furthermore, strain hardening through long chain branching is achieved by the process of the present invention. This is especially true in polyolefin compositions with a higher propylene polymer content, as indicated by the SHF parameters of Examples IE3, IE4 and IE6 and Comparative Examples CE2 to CE4. Considering the MFR 2 , strain hardening (SHF / MFR) can also be seen in IE1 and IE2 2 parameter).
[0262] For the embodiments of the present invention, it is also possible to directly or by considering the corresponding MFR 2 Observe that F 30 Melt strength and v 30 Improvement of melt stretchability.
[0263] Furthermore, for the propylene polymer content in the polyolefin composition, the crystallization temperature is increased by the process of the present invention.
Claims
1. A method for modifying a post-consumer recycled polyolefin composition comprising the steps of: (A) providing a post-consumer recycled polyolefin composition having an initial melt flow rate MFR2(1) measured at 230°C under 2.16 kg load according to ISO 1133 in the range of 1.0 to 100 g / 10 min, and based on the total weight of the post-consumer recycled polyolefin composition, as measured by FTIR spectroscopy, comprising (a) at least 50 wt.% of one or more propylene (co)polymer components, and (b) up to 50 wt. % of one or more ethylene (co)polymer components; (B) adding 0.10 to 1.50 wt % of a free radical initiator, based on the total weight of the post-consumer recycled polyolefin composition, to the post-consumer recycled polyolefin composition and optionally mixing the components to form a mixture (1); (C) adding 0.05 wt% to 0.50 wt% of a di-unsaturated hydrocarbon compound having the general formula (1) based on the total weight of the post-consumer recycled polyolefin composition (1) CH2=CH-(R)-CH=CH2, wherein R may be present or absent, and if present, R is an aliphatic or aromatic hydrocarbon group containing 1 to 6 carbon atoms, and mixing the components to form a mixture (2); as well as (D) extruding the mixture (2) at a temperature in the range of 180°C to 300°C to obtain a modified polyolefin composition having a final melt flow rate MFR2(2) measured according to ISO 1133 at 230°C under a load of 2.16 kg; The ratio of MFR2(2):MFR2(1) is below 1.
00.
2. The method according to claim 1, wherein the one or more propylene (co)polymer components comprise a propylene homopolymer, preferably an isotactic propylene homopolymer, and / or an isotactic copolymer of propylene and a comonomer selected from ethylene and / or one or more α-olefins having 4 to 10 carbon atoms, wherein the propylene (co)polymer components are prepared by quantitative 13 C{ 1 The copolymer preferably contains 0.1 to 27 mol % of the comonomer, as determined by H}-NMR spectroscopy.
3. The method according to any one of the preceding claims, wherein the one or more ethylene (co)polymer components comprise a copolymer of an ethylene homopolymer and / or ethylene and a comonomer selected from one or more alpha-olefins with 3 to 10 carbon atoms, wherein the copolymer is quantitatively 13 C{ 1 The copolymer preferably contains 0.1 to 20 mol % of comonomers as determined by H}-NMR spectroscopy, and wherein the melting enthalpy of completely crystalline polyethylene as determined by differential scanning calorimetry (DSC) is 293 J / g, and the ethylene homopolymer and / or the copolymer preferably has a crystallinity in the range of 40 to 90%.
4. The method according to any one of the preceding claims, wherein the post-consumer recycled polyolefin composition comprises, based on the total weight of the post-consumer recycled polyolefin composition, as determined by FTIR spectroscopy. (a) 50 to 98 wt% of one or more propylene (co)polymer components, and (b) 2 to 50 wt. % of one or more ethylene (co)polymer components.
5. The process according to any one of the preceding claims, wherein step (B) and / or step (C) is carried out at a temperature in the range of 20°C to 90°C.
6. The process according to any one of the preceding claims, wherein the doubly unsaturated hydrocarbon compound is 1,3-butadiene, and / or the free radical initiator is a peroxide compound, preferably selected from acyl peroxides, alkyl peroxides, hydroperoxides, peresters, peroxycarbonates and combinations thereof.
7. The method according to any one of the preceding claims, wherein the post-consumer recycled polyolefin composition further comprises one or more of the following, based on the total weight of the post-consumer recycled polyolefin composition: (c) 0.1 to 100 ppm, preferably 0.1 to 50 ppm, more preferably 0.1 to 20 ppm, most preferably 0.1 to 5 ppm limonene as determined by solid phase microextraction (HS-SPME-GC-MS); (d) 0.1 to 100 ppm fatty acids as determined by solid phase microextraction (HS-SPME-GC-MS); (e) 0.1 to 10 wt. % of a non-polyolefin polymer as determined by FTIR spectroscopy; (f) 0.1 to 10% by weight of other components selected from talc, chalk, carbon, calcium stearate, titanium dioxide, pigments, metals, glass, paper, wood and combinations thereof, measured as described in the specification.
8. The method according to any one of the preceding claims, wherein the post-consumer recycled polyolefin composition comprises a crystalline fraction (CF) determined according to the CRYSTEX QC method of ISO 6427 Annex B, in an amount ranging from 75 to 98 wt.-%, based on the total weight of the post-consumer recycled polyolefin composition.
9. The method according to any one of the preceding claims, wherein the post-consumer recycled polyolefin composition comprises an ethylene content in the crystalline fraction (C2(CF)) determined according to FTIR during CRYSTEX analysis, the ethylene content being in an amount ranging from 3 to 60 wt.-%, based on the total weight of the crystalline fraction of the post-consumer recycled polyolefin composition.
10. The method according to any one of the preceding claims, wherein the post-consumer recycled polyolefin composition is in the form of pellets having a median thickness T50 in the range of 0.5 to 5.0 mm as determined by direct caliper measurement.
11. The method according to any one of the preceding claims, wherein the method is characterized by providing at least one of the following properties: (1) the ratio of the amount of xylene heat insoluble (XHU) fraction of the modified polyolefin composition to the amount of xylene heat insoluble (XHU) fraction of the post-consumer recycled polyolefin composition, determined according to EN 579, is below 2.5; and (2) The ratio of MFR2(2):MFR2(1) is in the range of 0.01 to 0.
95.
12. A modified polyolefin composition obtainable by the process according to any one of the preceding claims.
13. The modified polyolefin composition of claim 12, wherein the modified polyolefin composition is characterized by at least one of the following properties: (1) F measured according to the Rheotens method of ISO 16790:2005 30 Melt strength ranges from 3.5 to 30.0 cN; (2) Determination of v according to the Rheotens method of ISO 16790:2005 30 Melt stretchability is in the range of 150 to 300 mm / s; (3) the amount of xylene heat insoluble (XHU) fraction determined according to EN 579 is in the range of 0.0 to 3.5 wt. %, based on the total weight of the modified polyolefin composition; (4) a second melt flow rate MFR2(2) measured according to ISO 1133 at 2.16 kg load and 230° C. in the range of 0.1 to 50.0 g / 10 min; (5) a molecular weight ratio Mw / Mn in the range of 5 to 15 as determined by GPC method according to ISO 16014-4:2003 and ASTM D 6474-99; and (6) As described in the instructions, -1 The strain hardening factor (SHF) measured at a strain rate of 2.0 and a Hencky strain of 2.5 and 180°C is in the range of 2.0 to 20.
0.
14. Use of the modified polyolefin composition according to any one of claims 12 and 13 in the manufacture of articles, preferably foamed articles, films or extrusion coatings.
15. An article comprising the modified polyolefin composition according to any one of claims 12 and 13, wherein the article is preferably a foamed article, a film or an extrusion coating, and comprises more than 50 wt% of the modified polyolefin composition based on the total weight of the article.
Citation Information
Patent Citations
Controlled rheology modified mixed-plastic polyethylene blend
EP3757152A1